PENGAWASAN SATUAN TUGAS SAPU BERSIH PUNGUTAN LIAR (SATGAS SABER PUNGLI) DI PROPINSI RIAU (STUDI KASUS DINAS KEHUTANAN) - Ravi Alwafi Vinky; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of this study is to analyze the implementation of the Satuan Tugas Sweep Pengap Liung (Satgas Saber Pungli) in the Riau Forestry Service. And to analyze the factors that inhibit the supervision of the Clean Sweep Task Unit (Satgas Saber Pungli) in the Riau Province Forestry Office. The type of research used is qualitative research, informant using snowball sampling technique and as informant in this research is Member of Satuan Tugas Sapu Bersih Pungutan Liar (Satgas Saber Pungli) Riau Province, Riau Forestry Office and Regional Office of Law and Human Rights Riau (Posko Saber Pungli ). The data type of this research is primary and secondary data with source of data from informant and documentation. While for data collection in research through interviews and documentation. Based on the result of the research, it can be seen that the form of supervision of Satuan Tugas Sapu Bersih Pungutan Liar (Satgas Saber Pungli) of Riau Province against illegal acts committed by the state apparatus in Riau Province outline through the community in the form of reports or public complaints in the implementation of public services. Supervision by the Clean Sweep Task Unit (Satgas Saber Pungli) Riau Province in accordance with the laws and regulations. One of the obstacles that hindered the illegal levy action because there has been no strict sanction in the form of direct dismissal without going through the judicial process for government officials who are proven to be caught red-handed. For that it is suggested in this study the officers (state apparatus) to carry out their duties in accordance with the authority and not abuse his power to seek profit from the community. To the government to presumably pay more attention to the criminal acts of illegal levies on the community because in this case the role of government is needed to eradicate the practice of illegal levies to roots. Keywords: Saber Pungli, Forest Service